2014 International Computer Science and Engineering Conference (ICSEC) 2014
DOI: 10.1109/icsec.2014.6978236
|View full text |Cite
|
Sign up to set email alerts
|

The flexible and adaptive X-mark detection for the simple answer sheets

Abstract: Template matching is a technique in digital image processing for finding a target object which matches the given template's pattern. This paper mainly aims to apply the template matching technique to check the answer sheet with multiple choices in order to reduce the cost of using an expensive machine called the Optical Mark Reader (OMR) machine as usual. Even more, the machine works with only a high hardness (or dark black) pencils such as ones with the hardness of 2B or higher. The technique of template matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…The projection profile and X-mark detection methods were not tested as they can only be used on boxes with ‘X’ marks. In any case, this type of input field is commonly used only in Thailand for public and school examination papers [ 3 , 4 ].…”
Section: Test Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The projection profile and X-mark detection methods were not tested as they can only be used on boxes with ‘X’ marks. In any case, this type of input field is commonly used only in Thailand for public and school examination papers [ 3 , 4 ].…”
Section: Test Resultsmentioning
confidence: 99%
“…Recent studies using different implementations of SOMR have reported error rates between 0.02–0.80% [ 3 5 , 7 , 17 20 ]. The error rate using the new detection method was 0.03% when tested on untrained respondents, which is in the lower end of the range compared to the others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations